Comparison of High School Student’s Learning Outcomes Using Cooperative Learning Model Between Think-Pair-Share (TPS) and Teams Games Tournament (TGT) Types on Reaction Equation - Nurlia L. Radjabani; Ratman Ratman; Purnama Ningsih (Universitas Tadulako, 2021)
This study aimed to describe the difference between students’ learning outcomes from the class using the cooperative learning model of think pair share (TPS) type and teams games tournament (TGT) type on the topic of reaction equation in class X at MAN 2 Model Palu. This study was a pre-experiment with the static group pretest-postest design. This study was conducted in two groups i.e., class XA as experiment group 1 (n = 24) and Class XB as experiment group 2 (n = 23). Data of students’ learning outcomes were analyzed using t-test two-party statistical analysis with the prerequisite of normality and homogeneity tests of the data from the given posttest. The analysis results obtained the average score of experimental class 1 (1X) was 68.25, while the average score of the control class (2X) was 63.15. The hypothesis test results obtained tcount = 2.47 and ttable = 2.02 with significance level = 0.05 and degrees of freedom 45, then H0 was rejected, and Ha was accepted. Based on these results, it can be concluded that students’ learning outcomes from the class using the cooperative learning model of think pair share (TPS) type is different from the class using cooperative learning model of teams games tournament (TGT) type on the topic of reaction equation in the Class X at MAN 2 Model Palu. Students' learning outcomes in experimental class 1 were higher than in experimental class 2.